A simplified binary harmony search algorithm for large scale 0–1 knapsack problems. Issue 12 (15th July 2015) - Kong, Xiangyong; Gao, Liqun; Ouyang, Haibin; Li, Steven
Highlights A difference based ingenious improvisation scheme is proposed. The pitch adjustment operator can be executed without requiring any parameters. A greedy repair procedure is introduced to ensure the availability of solutions. The proposed SBHS algorithm is easier for implementation. It is more effective and suitable for solving large scale 0–1 knapsack problems.